2006
DOI: 10.1093/heapro/dal053
|View full text |Cite
|
Sign up to set email alerts
|

Trade liberalization and the diet transition: a public health response

Abstract: Trade liberalization remains at the forefront of debates around globalization, particularly around the impact on agriculture and food. These debates, which often focus on how poorer countries can 'trade their way' out of poverty, pay limited attention to dietary health, especially in the light of the WHO's Global Strategy for Diet, Physical Activity and Health (2004), which warned that future health burdens will be increasingly determined by diet-related chronic diseases. This article examines the diet transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 8 publications
0
75
0
6
Order By: Relevance
“…19 The research conducted to date has revealed little about the factors that drive or contain the spread of fast food and obesity. 16 Some authors argue that the rising consumption of unhealthy foods seen worldwide has been facilitated by trade liberalization 20 and foreign investment in the food and beverage industries, 8,[21][22][23] which have resulted in the proliferation of large transnational food companies. 20,24,25 Offer et al have found that high-income countries with market-liberal welfare regimes -most of which are also English-speaking -have a higher prevalence of obesity and easier access to fast food.…”
Section: Introductionmentioning
confidence: 99%
“…19 The research conducted to date has revealed little about the factors that drive or contain the spread of fast food and obesity. 16 Some authors argue that the rising consumption of unhealthy foods seen worldwide has been facilitated by trade liberalization 20 and foreign investment in the food and beverage industries, 8,[21][22][23] which have resulted in the proliferation of large transnational food companies. 20,24,25 Offer et al have found that high-income countries with market-liberal welfare regimes -most of which are also English-speaking -have a higher prevalence of obesity and easier access to fast food.…”
Section: Introductionmentioning
confidence: 99%
“…There is widespread agreement that such downstream -and often unintended -consequences of trade policy making for health must be identified and described in order to ensure that appropriate complementary policies can be developed (4) . A further health implication of the trade liberalisation agenda is the facilitation of unhealthy consumption patterns related to the nutrition transition (4)(5)(6)(7)(8) . This transition is of growing concern in developing countries, where an observed convergence towards diets high in fat (particularly saturated fat) and sugar, and low in fibre has accompanied a rising burden of chronic disease (9,10) .…”
mentioning
confidence: 99%
“…There is a close correspondence between a rise in FDI and increased investments in processed foods. In Latin America, between 1988 and 1997, FDI in food industries grew from US$ 222 million to US $ 3.3 billion [37]. Supermarkets have focused on highly processed foods because of their long shelf lives and for the potential economies of scale [38].…”
Section: Specific Pathway Products Food Trade and Chronic Diseasementioning
confidence: 99%